PERSEPSI KONSUMEN TERHADAP KEGIATAN CSR DALAM INDUSTRI HOTEL DI PROVINSI BALI - Hermanto Yaputra; Yvonne Augustine Sudibyo (Jurnal Manajemen dan Pemasaran Jasa, 2019)
This paper investigates the influence of economic, social, and environmental factors on Corporate Social Responsibility (CSR). This research is a quantitative research using 200 respondents. The Structural Equation Model method is used to analyze data by using hypothesis testing. The finding of this research is that the three main indicators; economic, social and environmental significantly influence CSR. The theoretical implication of this research is that CSR is influenced by consumer perception. Whereas the managerial implication is that the companies managers may adopt the result of this research, especially to increase the quality of the CSR program.